Comparison of Effects of Light Anesthetics, Diethyl Ether and Carbon Dioxide, on Hypothalamic Paraventricular Nucleus D1 and D2 Dopamine Receptors- and Glucosensitive Neurons-Induced Food Intake in Fasted Conscious Rats - Masoud Shareghi Brojeni; Morteza Salimi; Zahra Mirmohammadsadeghi; Abbas Haghparast; Afsaneh Eliassi (Basic and Clinical Neuroscience, 2018)
Introduction: Carbon Dioxide (CO2) and diethyl ether are used as light anesthetics. However, experimental data about their side effects are scarce. In addition, in all our previous works on regulatory mechanisms of hypothalamus during food intake, including the effect of Paraventricular Nucleus (PVN) D1 and D2 dopamine receptors and glucosensitive neurons, the drug injections were performed under brief diethyl ether anesthesia. In the current study, we tested the hypothesis which postulates that CO2 and diethyl ether as light anesthetic agents affect the stimulatory effect of PVN dopamine receptors and glucosensitive neurons in feeding behavior. Methods: Male Wistar rats were implanted with guide cannula directed to their PVN. Glucose (0.8 µg), SKF38393 (D1 agonist, 0.5 µg), quinpirole (D2 agonist, 0.3 µg) and saline (0.3 µL) were microinjected into the PVN and food intake was measured over 1 hour. Results: Our results showed that CO2 but not diethyl ether decreased food intake compared to intact animals. The PVN injections of glucose, SKF38393, and quinpirole increased food intake under brief diethyl ether anesthesia. In contrast, the PVN microinjected glucose-induced and dopamine receptor agonists-induced food intake were inhibited under light CO2 anesthesia. Conclusion: Our results suggest that brief exposure to CO2 and diethyl ether as light anesthetic agents may affect PVN glucosensing neurons-induced and dopamine receptors-induced food intake in fasted rats.